Comparison of the Effects of Dibutyl and Monobutyl Phthalates on the Steroidogenesis of Rat Immature Leydig Cells - Li, Linxi (Biomed Res Int, 2016)
Dibutyl phthalate (DBP) is a widely used synthetic phthalic diester and monobutyl phthalate (MBP) is its main metabolite. DBP can be released into the environment and potentially disrupting mammalian male reproductive endocrine system. However, the potencies of DBP and MBP to inhibit Leydig cell steroidogenesis and their possible mechanisms are not clear. Immature Leydig cells isolated from rats were cultured with 0.05–50 μM DBP or MBP for 3 h in combination with testosterone synthesis regulator or intermediate. The concentrations of 5α-androstanediol and testosterone in the media were measured, and the mRNA levels of the androgen biosynthetic genes were detected by qPCR. The direct actions of DBP or MBP on CYP11A1, CYP17A1, SRD5A1, and AKR1C14 activities were measured. MBP inhibited androgen production by the immature Leydig cell at as low as 50 nM, while 50 μM was required for DBP to suppress its androgen production. MBP mainly downregulated Cyp11a1 and Hsd3b1 expression levels at 50 nM. However, 50 μM DBP downregulated Star, Hsd3b1, and Hsd17b3 expression levels and directly inhibited CYP11A1 and CYP17A1 activities. In conclusion, DBP is metabolized to more potent inhibitor MBP that downregulated the expression levels of some androgen biosynthetic enzymes.